2021
DOI: 10.3390/nano11123257
|View full text |Cite
|
Sign up to set email alerts
|

Homing Peptide-Based Targeting of Tenascin-C and Fibronectin in Endometriosis

Abstract: The current diagnostic and therapeutic strategies for endometriosis are limited. Although endometriosis is a benign condition, some of its traits, such as increased cell invasion, migration, tissue inflammation, and angiogenesis are similar to cancer. Here we explored the application of homing peptides for precision delivery of diagnostic and therapeutic compounds to endometriotic lesions. First, we audited a panel of peptide phages for the binding to the cultured immortalized endometriotic epithelial 12Z and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The authors showed in a previous study that a peptide that binds to TNC-C and Fn-EDB (PL1 peptide) effectively inhibited the growth of glioblastoma ( Lingasamy et al, 2019 ). Considering the similarities in the pathogeneses of tumours and endometriosis, the author inferred the strong effect of the PL1 peptide to target endometriosis for its treatment in this study ( Simón-Gracia et al, 2021 ). First, they synthesized the PL1 peptide with silver nanoparticles (PL1-AgNPs) and found that PL1-AgNPs were internalized into 12Z and HESC cells, which highly expressed the PL1 peptide receptors TNC-C and Fn-EDB.…”
Section: Nanomaterial-based Drug Therapymentioning
confidence: 85%
See 1 more Smart Citation
“…The authors showed in a previous study that a peptide that binds to TNC-C and Fn-EDB (PL1 peptide) effectively inhibited the growth of glioblastoma ( Lingasamy et al, 2019 ). Considering the similarities in the pathogeneses of tumours and endometriosis, the author inferred the strong effect of the PL1 peptide to target endometriosis for its treatment in this study ( Simón-Gracia et al, 2021 ). First, they synthesized the PL1 peptide with silver nanoparticles (PL1-AgNPs) and found that PL1-AgNPs were internalized into 12Z and HESC cells, which highly expressed the PL1 peptide receptors TNC-C and Fn-EDB.…”
Section: Nanomaterial-based Drug Therapymentioning
confidence: 85%
“…(A) Confocal fluorescence images of cellular internalization of PL1-AgNPs or biotin-AgNPs in12Z spheroids for 1, 2, 4, and 20 h. (B) Morphological images of 12Z spheroids incubated with PL1-MMAE-NPs or biotin MMAE-AgNPs for 24, 48, and 72 h. (C) Cell viability of 12Z spheroids incubated with different concentrations of PL1-MMAE-AgNPs or biotin-MMAE-AgNPs for 72 h * p < 0.05. Reprinted with permission from ( Simón-Gracia et al, 2021 ).…”
Section: Nanomaterial-based Drug Therapymentioning
confidence: 99%
“…In fact, animal models cannot always reproduce all the features of some diseases, and a non-animal-based model could better reproduce the human microenvironment. 155,156 A challenging 3D in vitro model has been proposed by Simon Garcia 56 and others. 157 A 3D model recreates the highly inflammatory microenvironment of endometriosis better than monolayer models since it includes different cell types and stimuli, allowing us to explore the cell complex while helping to reduce the number of animals used.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the ability of AgNPs loaded with the antimitotic drug monomethyl auristatin E (MMAE) to suppress the viability of endometriotic cells cultured in 2D, and as spheroids in a peptide-dependent manner. 56 Moreover, Park et al devised iron oxide magnetic NPs (MN) coupled with a kinase insert domain receptor (KDR) able to accumulate in endometriotic lesions targeting vascular endothelial growth factor receptor 2 (VEGFR-2) (Fig. 2B).…”
Section: Emerging Therapeutic and Theranostic Nanotechnology Approach...mentioning
confidence: 99%
See 1 more Smart Citation